Automated Detection of Diabetic Retinopathy through Blood Vessel and Micro-aneurysms - Renu,; Kumar, Sachin; Mishra, Sumita; Pragya, (International Journal of Computer Sciences and Engineering, 2025)
Vision is the way we access, appreciate and interpret the world. Diabetic retinopathy is one of the common diseases which if remain undetected; causes blindness. Micro aneurysm is the first visible sign of Diabetic retinopathy; which appears like a tiny blood droplet on retinal fundus images. The bunches of Micro aneurysms may be examined to indicate the severity of the disease. The incidence of blindness caused by diabetes mellitus reduces by the early detection of MAs. This paper presents a novel approach for the automated detection of DR from fundus images using blood vessel perimeter measurement and Micro aneurysms count. The suggested method correctly identifies Micro aneurism even in poor quality image.